Prostaglandin E(2) Inhibits Human Lung Fibroblast Chemotaxis through Disparate Actions on Different E-Prostanoid Receptors - Li, Ying-Ji (American Thoracic Society, 2011)
The migration of fibroblasts is believed to play a key role in both normal wound repair and abnormal tissue remodeling. Prostaglandin E (PGE)(2), a mediator that can inhibit many fibroblast functions including chemotaxis, was reported to be mediated by the E-prostanoid (EP) receptor EP2. PGE(2), however, can act on four receptors. This study was designed to determine if EP receptors, in addition to EP2, can modulate fibroblast chemotaxis. Using human fetal lung fibroblasts, the expression of all four EP receptors was demonstrated by Western blotting. EP2-selective and EP4-selective agonists inhibited both chemotaxis toward fibronectin in the blindwell assay and migration in a wound-closure assay. In contrast, EP1-selective and EP3-selective agonists stimulated cell migration in both assay systems. These results were confirmed using EP-selective antagonists. The role of both EP2 and EP4 receptors in mediating the PGE(2) inhibition of chemotaxis was also confirmed by small interfering RNA suppression. Furthermore, the role of EP receptors was confirmed by blocking the expected signaling pathways. Taken together, these results demonstrate that PGE(2) can act on multiple EP receptors in human lung fibroblasts, to exert disparate effects. Alterations in EP receptor expression may have the potential to alter PGE(2) action. Targeting specific EP receptors may offer therapeutic opportunities in conditions characterized by abnormal tissue repair and remodeling.